Athletes' Perception of Parental Support and Achievement Motivation: A Correlational Study with Early Age Individual Sport Athletes in Swimming - Fadluloh, Firmansyah Mujahid; Sartono, Hadi; Kusumah, Widi; Mulyana, Mulyana (Universitas Majalengka, 2024)
Parents are very important in helping their athletes develop, especially young athletes, as this can influence the development of their skills to achieve a high level of performance. Parental involvement in supporting their athlete's performance influences many aspects, such as motivation, which is generally thought to include the initiation, direction, intensity, and persistence of a person's behavior. Parental involvement also affects the athlete's confidence and independence in training. The aim of the research is to investigate how parental support influences the desire of young athletes to excel in the sport of swimming Bandung Regency. A quantitative descriptive method is used in this research, which is designed as correlational research. In this study, 20 swimmers from the SR Swimming Club in Bandung Regency were selected as the research sample. The research instrument uses two questionnaires, each consisting of 36 items about parental support and 30 items about motivation for achievement. Athletes fill out this questionnaire through a Google Form, using a Likert scale as the answer choice option. The Spearman rank correlation test is used in version 25 of SPSS to process and analyze data. The study's findings show that parental support has a significant correlation with the desire of young athletes to excel in swimming In Bandung Regency. So, it can be concluded that young athletes will be more motivated to excel in the sport of swimming Bandung Regency with good parental support.